Abundance and activity of soil ammonia oxidizing microorganisms in colombian crops of economic importance (2017)
Nitrification rates, real-time quantitative PCR assay of AOA/AOB were coupled with a biological nitrification soil bioassay to revealed the nitrifiers abundance and potential BNI activity in different Colombian crop soils of economic importance: Rice (Oriza sativa), Maize (Zea mays), Common beans (Phaseolus vulgaris), Sugar cane (Saccharum officinarum),Cassava (Manihot esculenta), Brachiaria humidicola and 5 silvopastoral systems. The N initial quantification of NO3- and NR revealed significant differences between crops by the moment of soil sampling and stimulation of microorganism's activity. However, there was not an evident correlation between NR and abundances of AOA/AOB populations in all the crops evaluated as it was expected. The present results support the previous suggested importance of BNI as a strategy to manage N input in agricultural systems because agricultural management can strongly influence soil microbial activity and composition